Photodynamic therapy of tumour cells mediated by the natural anthraquinone parietin and blue light - Mugas, María Laura (2021)
Photodynamic therapy (PDT) is a treatment for superficial tumours involving the administration of a photosensitiser followed by irradiation. The potential of the natural anthraquinone parietin (PTN) in PDT is still relatively unexploited. In the present work, PTN isolated from the lichen Teoloschistes nodulifer (Nyl.) Hillman (Telochistaceae) was evaluated as a potential photosensitiser on tumour cells employing UVA-Vis and blue light. Blue light of 2 J/cm2 induced 50% death of K562 leukaemic cells treated 1 h with 30 μM PTN (Protocol a). Higher light doses (8 J/cm2) were needed to achieve the same percentage of cell death employing lower PTN concentrations (3 μM) and higher exposure times (24 h) (Protocol b). Cell cycle analysis after both protocols of PTN-PDT revealed a high percentage of sub-G1 cells. PTN was found to be taken up by K562 cells mainly by passive diffusion. Other tumour cells such as ovary cancer IGROV-1 and LM2 mammary carcinoma, as well as the normal keratinocytes HaCaT, were also photosensitised with PTN-PDT. We conclude that PTN is a promising photosensitiser for PDT of superficial malignancies and purging of leukaemic cells, when illuminated with blue light. Thus, this light wavelength is proposed to replace the Vis-UVA lamps generally employed for the photosensitisation of anthraquinones.